Desert Bel Air residential complex - William F. Cody:::::: (1961)
Large reproduction of a presentation drawing with additional hand-colored additions (possibly pencil and/or pastels). Desert Bel Air proposed residential complex, Job # 6109 in what is now Indian Wells.